2020
DOI: 10.1097/brs.0000000000003924
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes After Single-level Coflex Interspinous Implants Versus Single-level Laminectomy

Abstract: Study Design. Retrospective cohort analysis.Objective. The aim of this study was to compare postoperative outcomes of Coflex interspinous device versus laminectomy. Summary of Background Data. Coflex Interlaminar Stabilization device (CID) is indicated for one-or two-level lumbar stenosis with grade 1 stable spondylolisthesis in adult patients, as an alternative to laminectomy, or laminectomy and fusion. CID provides stability against progressive spondylolisthesis, retains motion, and prevents further disc spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Doo et al [32] conducted a clinical trial and showed that Coflex was indicated for patients with lumbar spinal stenosis with mild associated segmental instability and had less effect on adjacent segments than conventional posterior lumbar interbody fusion (PLIF) procedures. In their retrospective study, Zhong et al [33] examined 83 patients and observed that the utilization of single-level Coflex was linked to elevated rates of overall complications, longer operative time, and extended hospital stay within a three-month period in comparison to fenestration decompression alone. The StenoFix system, akin to the Coflex system, exhibits a “w” shape from a lateral perspective, thereby enabling it to withstand greater axial loads.…”
Section: Discussionmentioning
confidence: 99%
“…Doo et al [32] conducted a clinical trial and showed that Coflex was indicated for patients with lumbar spinal stenosis with mild associated segmental instability and had less effect on adjacent segments than conventional posterior lumbar interbody fusion (PLIF) procedures. In their retrospective study, Zhong et al [33] examined 83 patients and observed that the utilization of single-level Coflex was linked to elevated rates of overall complications, longer operative time, and extended hospital stay within a three-month period in comparison to fenestration decompression alone. The StenoFix system, akin to the Coflex system, exhibits a “w” shape from a lateral perspective, thereby enabling it to withstand greater axial loads.…”
Section: Discussionmentioning
confidence: 99%
“…Interspinous process devices expand the aperture of the intervertebral foramina and maintain partial segmental range of motion, achieving a good balance between adequate decompression and stability [13,14] . First introduced in 1994, Co ex dynamic interlaminar stabilization has been shown to provide results comparable to those of surgical decompression and fusion and can be regarded as an effective alternative treatment [15][16][17] . BacFuse is another interspinous process device which differs from Co ex in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…[32] 2016 55/51.8 28/25 Coflex Decompression 12/12 Jack, Z. [33] 2021 69/64. CI: −4.75-1.03, P = .21; Fig.…”
Section: Visual Analog Scale Pain Scorementioning
confidence: 99%